ANALISIS PENERAPAN GREEN CAMPUS BERDASARKAN UI GREENMETRIC PADA FAKULTAS TEKNIK UNIVERSITAS PATTIMURA AMBON - Pertiwi, Hana; Buyang, Christy Gery; Sangadji, Fauzan A (JURNAL SIMETRIK, 2025)
The University of Indonesia launched the UI GreenMetric World University Ranking in 2010 as a benchmark for evaluating green campuses. The goal of the college community's "green campus" idea is to lessen its negative environmental effects by implementing programs like garbage recycling, green mobility, energy and water conservation, and climate change mitigation. Arrangement and infrastructure (15%), energy and climate change (21%), waste (18%), water (10%), transportation (18%), and education and research (18%) are the six assessment criteria for UI GreenMetric. The purpose of this research is to examine how the Unpatti Engineering Faculty has implemented the green campus idea by using the UI GreenMetric 2022 categories and indicators. This study employed a quantitative descriptive analytical approach. Two types of data were used: primary and secondary. Primary data came from field observations, measurements, and interviews. Secondary data was gathered from faculty members already in the field as well as information on sustainability issues, waste recycling, energy and water conservation, and other topics not covered by primary data collection. According to the study's findings, the planning and infrastructure (SI) category received 510 points, the energy and climate change (EC) category received 560 points, the waste and water (WR) categories received 0 points, the transportation (TR) category received 450 points, and the education and research (ED) category received 400 points. The Unpatti Engineering Faculty's green campus implementation study, as determined by the UI GreenMetric evaluation, yielded a total score of 1920 points out of a possible 10,000 points, or 19.20% out of 100%. Keywords: UI GreenMetric; Green Campus; Faculty of Engineering Unpatti